Implementation of Hands on Minds on Integrated Electronic Student Worksheets on Environmental Change Material to Improve Critical Thinking Skills of 10th Grade Students at Nation Star Academy Surabaya - Aulia Izzaty Karima; Herlina Fitrihidajati (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2026)
The current curriculum requires students to not only master knowledge, but also be able to solve real-world problems through the development of 21st-century skills, particularly the 4Cs (Critical Thinking, Communication, Collaboration, and Creativity). Indonesian students' critical thinking skills are still relatively low, according to the 2022 Programme for International Student Assessment (PISA) results. Therefore, there is a need for innovative learning media that can optimally train critical thinking skills. This study aims to describe learning completeness, consistency in the application of the integrated Hands On Minds On E-LKPD, and student responses to its use in the learning process. This study uses a quantitative descriptive approach with a Pre-Experimental One Group Pre-test and Post-test Design method. The research subjects involved 50 tenth-grade students from two classes at Nation Star Academy (NSA) Surabaya who use the Cambridge curriculum. The research was conducted in October 2025 during three meetings. The research instruments were pre-tests and post-tests to measure learning completeness and improvement, as well as student response questionnaires. The average post-test score reached 94% above the minimum passing grade with an N-Gain value of 0.88, which is categorized as high. Student responses to the use of E-LKPD were very positive at 92%. Thus, it can be concluded that the implementation of E-LKPD integrated with Hands On Minds On, carried out in accordance with the Problem Based Learning syntax, is effective in improving students' critical thinking skills.